Yearning to belong Malaysia's Indian Muslims, Chitties, Portuguese Eurasians, Peranakan Chinese, and Baweanese - Pillai, Patrick (ISEAS - Yusof Ishak Institute, 2015)
This book uncovers some of this fascinating diversity through the stories of five little-known acculturated ethnic groups in Peninsula Malaysia. The author, a Malaysian sociologist, delivers an insightful and lucid study of these groups, with some surprising findings.